1994
DOI: 10.1016/0009-8981(94)90206-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of artificial intelligence in analytical systems for the clinical laboratory

Abstract: Glostrup/Copehagen, Denmark. segmented flow system started with the auto-analysers of Skeggs [2], that were made commercially available at the end of the 1950s. This process has continued through many phases with the most recent advances being in the area of robotics [3]. Mechanization figure) and the open or stand-alone system (total figure). Metarules are part of the procedural knowledge of expert systems. They are used to evoke programs and to guide the inference process and thus define how to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…They were used as an alternative to the traditional multivariate statistical techniques for the analysis of feature extracted parameters (16,18). They were used as an alternative to the traditional multivariate statistical techniques for the analysis of feature extracted parameters (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They were used as an alternative to the traditional multivariate statistical techniques for the analysis of feature extracted parameters (16,18). They were used as an alternative to the traditional multivariate statistical techniques for the analysis of feature extracted parameters (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, new algorithms are being suggested for medical pattern recognition tasks (14)(15)(16). Beside the algorithm based expert systems, we can now evaluate biological signals with non-linear techniques simulating biological pattern recognition procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the best of these interpretation programs perform almost as well as human experts (Willems et al, 1991). Computer-aided decision making has been used in many other applications, for example image interpretation (Scott, 1993;Kahn, 1994), and in the clinical laboratory (Place et al, 1994). The standard methods for classifying clinical data have been knowledge-based systems and statistical methods such as linear discriminant analysis.…”
Section: Introductionmentioning
confidence: 99%